Studi Kelayakan Implementasi SAP dengan Metode Fit/Gap Analysis dan CBA - Nurlina, Nurlina (ComTech: Computer, Mathematics and Engineering Applications, 2013)
An application system is required by a company to meet the needs of enterprise business processes so as to provide information quickly and accurately. Therefore, it is necessary to study the feasibility status of plan of enterprise system implementation. SAP R/3 contains various modules which is deserved to be considered as a company's information system solution. Results of the feasibility study through the analysis of fit/ gap analysis state that the implementation of SAP R/3 sales module is feasible and able to meet all the needs of the system.Results of cost and benefit analysis state that the strategy implementation of SAP R/3 module is feasible. Based on the analysis and research using the two methods above, a decision can be taken whether the SAP R/3 is worth to be implemented or not.